Remarkable anecdotes illustrating the nature and effect of seizure-precipitating factors in Border Collies with idiopathic epilepsy - Mandigers, Paul J. J.; Santifort, Koen M. (Frontiers in Veterinary Science, 2023)
Epilepsy is one of the most common chronic neurological syndrome in dogs and has serious implications on the quality of life of both the dogs and owners. Seizure-precipitating factors (SPFs) (also termed ‘triggers’ or ‘provocative factors’) have been studied and reported in both humans and dogs with idiopathic epilepsy. In dogs stress, hormones, sleep-deprivation, and the weather have been reported as SPFs. The Border Collie (BC) is a dog breed that is predisposed to idiopathic epilepsy and the outcome is often poor. BCs are described as a very sensitive dogs with a strong focus on their owners, and this may have influence on their and their owners’ stress level. In this article, we describe six unrelated BCs with idiopathic epilepsy in which several remarkable SPFs were identified and avoiding them improved the outcome of these dogs. The possible SPFs were for each dog different. The SPFs were among others the other dog in the family, the lack of intellectual challenge, the presence of an autistic child, a busy street, the relation with the owner and throwing a ball at the beach. These cases illustrate that recognizing the SPF(s), and taking measures with regard to management can lead to a reduction in epileptic seizure frequency or even achieving seizure freedom.